Pengaruh Pembiayaan Murabahah Terhadap Pendapatan UMKM (BMT Al Bahjah Kuningan) - Millah, Aep Syaeful (Maro: Jurnal Ekonomi Syariah dan Bisnis, 2025)
Indonesia’s micro, small, and medium enterprises (MSMEs) are important in national economic development. Through financing at BMT, MSMEs can develop their businesses according to expectations. This research was conducted to analyze the magnitude of the influence of murabahah financing on MSME income in BMT Al Bahjah District. Brass. The method used in this research is a type of quantitative research. This research uses a saturated sampling technique. The total sample was 40 respondents who were customers or members who obtained murabahah financing. The data collection method used in this research was a questionnaire. The data obtained was processed using SPSS software. The data analysis method uses the normality test, simple linear regression analysis, coefficient of determination (R²), and significant T-test. The results of this study show that the murabahah financing variable has a positive and significant effect on MSME income with a calculated t value = 8.716 > t table = 2.024 and the significant value is 0.000 <0.05. The limitation of this research is the use of only one variable, namely murabahah financing, and its limited scope.